Cloning of the repertoire of individual Plasmodium falciparum var genes using Transformation Associated Recombination (TAR) - Gaida, Annette; Becker, Marion M.; Schmid, Christoph D.; Bühlmann, Tobias; Louis, Edward J.; Beck, Hans-Peter (Public Library of Science, 2011)
One of the major virulence factors of the malaria causing parasite is the Plasmodium falciparum encoded erythrocyte membrane protein 1 (PfEMP1). It is translocated to It the membrane of infected erythrocytes and expressed from approximately 60 var genes in a mutually exclusive manner. Switching of var genes allows the parasite to alter functional and antigenic properties of infected erythrocytes, to escape the immune defense and to establish chronic infections. We have developed an efficient method for isolating VAR genes from telomeric and other genome locations by adapting transformation-associated recombination (TAR) cloning, which can then be analyzed and sequenced. For this purpose, three plasmids each containing a homologous sequence representing the upstream regions of the group A, B, and C var genes and a sequence homologous to the conserved acidic terminal segment (ATS) of var genes were generated. Co-transfection with P. falciparum strain ITG2F6 genomic DNA in yeast cells yielded 200 TAR clones. The relative frequencies of clones from each group were not biased. Clones were screened by PCR, as well as Southern blotting, which revealed clones missed by PCR due to sequence mismatches with the primers. Selected clones were transformed into E. coli and further analyzed by RFLP and end sequencing. Physical analysis of 36 clones revealed 27 distinct types potentially representing 50% of the var gene repertoire. Three clones were selected for sequencing and assembled into single var gene containing contigs. This study demonstrates that it is possible to rapidly obtain the repertoire of var genes from P. falciparum within a single set of cloning experiments. This technique can be applied to individual isolates which will provide a detailed picture of the diversity of var genes in the field. This is a powerful tool to overcome the obstacles with cloning and assembly of multi-gene families by simultaneously cloning each member.